Calcium phosphate–calcium titanate composite coatings for orthopedic applications. Issue 8 (June 2016) - Arce, J. Esguerra; Arce, A. Esguerra; Aguilar, Y.; Yate, L.; Moya, S.; Rincón, C.; Gutiérrez, O.
Abstract: Novel bioactive calcium titanate–tricalcium phosphate–tetracalcium phosphate composite coatings were developed. Powder mixtures of hydroxyapatite and 25, 50 and 75 vol% of calcium titanate were uniaxially pressed and sintered at 1100–1200 °C for 4 h. After heat treatment, the composites, which consisted of calcium titanate and oxyhydroxyapatite (Ca10 (PO4 )6 (OH)2−2 x O x □ x ), were evaporated by magnetron sputtering to coat an AISI 304/Ti buffer layer substrate. Calcium phosphate (CP) and calcium titanate (CT) coatings were also produced for comparison. The surface topography of the composite coatings was observed by SEM and AFM. Their structure and composition were evaluated by XRD, FTIR and XPS, and the re-assembly process of the atoms from composite targets to the coatings was emphasized. Nanoindentation experiments were carried out to measure the hardness. Coated samples were immersed in a simulated body fluid (SBF) for 30 days under physiological conditions of pH and temperature for the in-vitro bioactivity assessment. Finally, because the coatings are proposed for orthopedic applications, the cytotoxicity of the coatings was examined with human osteoblasts. It was found that calcium titanate coating is harder than the calcium phosphate coating, the 75–25 composite coatings fit a rule of mixture of hardness, and the rougher coatings contained a larger amount of nano-scale precipitated apatite. Furthermore, all the coatings were not cytotoxic. The results indicate that 75%CP–25%CT coating is a potential material for bone tissue replacement and regeneration.